2016
DOI: 10.1016/j.chom.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

A Viral Deamidase Targets the Helicase Domain of RIG-I to Block RNA-Induced Activation

Abstract: SUMMARY RIG-I detects double-stranded RNA (dsRNA) to trigger antiviral cytokine production. Protein deamidation is emerging as a post-translational modification that chiefly regulates protein function. We report here that UL37 of herpes simplex virus 1 (HSV-1) is a protein deamidase that targets RIG-I to block RNA-induced activation. Mass spectrometry analysis identified two asparagine residues in the helicase 2i domain of RIG-I that were deamidated upon UL37 expression or HSV-1 infection. Deamidation rendered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
118
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(125 citation statements)
references
References 52 publications
7
118
0
Order By: Relevance
“…We previously reported that the UL37 tegument protein of HSV-1 deamidates RIG-I to avoid dsRNA-induced innate immune activation (Zhao et al, 2016b). Recombinant HSV-1 carrying the deamidase-inactivating UL37C819S mutation (HSV-1 UL37C819S) more robustly induced antiviral cytokines than HSV-1 containing UL37 wild-type (HSV-1 UL37WT), while they replicated comparatively in VERO cells that are defective in type I interferon production (Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that the UL37 tegument protein of HSV-1 deamidates RIG-I to avoid dsRNA-induced innate immune activation (Zhao et al, 2016b). Recombinant HSV-1 carrying the deamidase-inactivating UL37C819S mutation (HSV-1 UL37C819S) more robustly induced antiviral cytokines than HSV-1 containing UL37 wild-type (HSV-1 UL37WT), while they replicated comparatively in VERO cells that are defective in type I interferon production (Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that UL37 deamidates RIG-I to avoid dsRNA-induced innate immune activation (Zhao et al, 2016b). To discern the contribution of RIG-I and cGAS to host defense against HSV-1, we generated primary bone marrow-derived macrophages (BMDMs) from WT, MAVS −/− and cGAS −/− mice and examined innate immune response upon infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4A), thus preventing activation of the inflammasome (129,130). In addition, the viral-encoded enzyme UL37 (unique long region 37) deamidates two asparagine residues in RIG-I that are critical for the ability of RIG-I to bind to double-stranded RNA (131). Consequently, this RLR-type sensor (Fig.…”
Section: Viral Immune Evasion and Potential Counteraction By Il-36mentioning
confidence: 99%
“…3A) is not activated, and production of antiviral IFN-b is inhibited (131). Although whether or not HSV-1 UL37 has an effect upon IL-1b and IL-18 activation was not examined in this study (131), the viral immune evasion strategy that was identified is likely to also affect these proinflammatory cytokines due to the known role of RIG-I in inducing their inflammasome-dependent processing (132). Finally, IL-1b that has been processed is retained within HSV-1-infected cells (Fig.…”
Section: Viral Immune Evasion and Potential Counteraction By Il-36mentioning
confidence: 99%